(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2012)
Proceedings of the Palermo Workshop "New Developments on Triassic Integrated Stratigraphy" Palermo, September 12-16, 2010 A review of the Halobia faunas and biostratigraphy of the uppermost Carnian – lowermost Norian of western Sicily is provided, through the study 166 fossiliferous beds of the 143 metres thick Pizzo Mondello Scillato Formation succession. The major role of the halobiids as biostratigraphic markers and tools for global correlations at the Carnian/Norian boundary is described. New morphometrical data on the ten species (Halobia carnica, H. lenticularis, H. cf. rugosa, H. radiata, H. simplex, H. superba, H. austriaca, H. styriaca, H. beyrichi, and H. mediterranea) occurring in this time interval are provided, as well as a revision of the correlations between western Sicily, the rest of the Tethys and North America. The Halobia lenticularis zone corresponds to the Anatropites spinosus ammonoid zone, the Halobia radiata zone spans the Carnian/Norian boundary interval, and the Halobia austriaca, Halobia styriaca and Halobia beyrichi zones correspond to the Guembelites jandianus ammonoid zone. The correlation of the distributions of these ten forms with those from other sections in both Tethys and North America allow to recognise the key role of Halobia austriaca as best halobiid marker for the definition of the base of the Norian GSSP.